Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3396/ijic.v12i2.012.16
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, phenotypic and genotypic characterization of carpabenem resistant Enterobacteriaceae in Tanta University Hospitals, Egypt

Abstract: Carpabenem resistant Enterobacteriacae (CRE) is an increasing worldwide health problem with excess morbidity and mortality. So the aim of this work to study the risk factors, phenotypic and genotypic characters of CRE in our institute. Seventy five patients with hospital acquired infection were enrolled in this study. Identification and susceptibility testing were performed. The differentiation of the types of carbapenemases was done by inhibitor-based tests. The bla genes were detected by using the multiplex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 0 publications
6
17
0
Order By: Relevance
“…This high frequency of MBL in Khartoum state is a result of the excessive use of meropenem in the treatment of patients associated with ESBL infections. This nding agrees with a study in Egypt, which reported that carbapenem resistance rate was 62.7% among Enterobacteriaceae (17). High rates of carbapenem resistance haves also been observed in Uganda in a study conducted by Okoche in 2015.…”
Section: Discussionsupporting
confidence: 91%
“…This high frequency of MBL in Khartoum state is a result of the excessive use of meropenem in the treatment of patients associated with ESBL infections. This nding agrees with a study in Egypt, which reported that carbapenem resistance rate was 62.7% among Enterobacteriaceae (17). High rates of carbapenem resistance haves also been observed in Uganda in a study conducted by Okoche in 2015.…”
Section: Discussionsupporting
confidence: 91%
“…This result shows accordance with El-Sweify et al [15] who reported carbapenem resistance in 44.3% of K. pneumoniae isolates in SCUHs. Higher results were detected by Melake et al [16] and Amer et al [17] as they reported 62.5% and 62.7% carbapenemresistance among K.pneumoniae and Enterobactereciae isolates. On the other hand, lower results of carbapenem resistance were also reported in different studies as Khare et al [18] and Okoche et al [19] reported 37.9% and 28.6% carbapenem resistance.…”
Section: Klebsiellamentioning
confidence: 67%
“…(Ethiopia), Okoche D et al 13 (Uganda), Amer WH et al 14 (Egypt), Camara A et al 15 (Senegal), and Wartiti MA et al 16 (Morocco) which reported the prevalence of CRE were 15.2%, 12.12%, 28.6%, 62.7%, 5.1%, and 2.8% respectively. 11−16…”
Section: Introductionmentioning
confidence: 97%